Global Financial Spillovers to Emerging Market Sovereign Bond Markets - Ebeke, Christian; Kyobe, Annette (Washington, D.C. : International Monetary Fund, 2015)
Foreign holdings of emerging markets (EMs) government bonds have increased substantially over the last decade. While foreign participation in local-currency sovereign bond markets provides an additional source of financing and reduces sovereign yields, it raises concerns about increased sensitivity of yields to shifts in market sentiment. The analysis in this paper suggests that foreign participation and an undiversified investor base transmit global financial shocks to local-currency sovereign bond markets by increasing yield volatility and, beyond a certain threshold, amplify these spillovers. These estimates are robust to a range of econometric techniques including panel smooth threshold regression.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet